2020
DOI: 10.1002/elps.201900396
|View full text |Cite
|
Sign up to set email alerts
|

Ion current rectification behavior of a nanochannel having nonuniform cross‐section

Abstract: Ion current rectification behavior of a nanochannel having nonuniform cross-sectionDue to its versatile applications in biotechnology, ion current rectification (ICR), which arises from the asymmetric nature of the ion transport in a nanochannel, has drawn much attention, recently. Here, the ICR behavior of a pH-regulated nanochannel comprising two series connected cylindrical nanochannels of different radii is examined theoretically, focusing on the influences of the radii ratio, the length ratio, the bulk co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…ICR can be induced by asymmetry in nanopore geometry, as done in conically shaped nanopores, 2 as well as nanopores with stepped cross-section. 12 Asymmetric surface properties of nanopores, e.g. asymmetric charge density, 13 wettability 14 and slip length 15 of surfaces along the pore axis can also produce ICR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICR can be induced by asymmetry in nanopore geometry, as done in conically shaped nanopores, 2 as well as nanopores with stepped cross-section. 12 Asymmetric surface properties of nanopores, e.g. asymmetric charge density, 13 wettability 14 and slip length 15 of surfaces along the pore axis can also produce ICR.…”
Section: Introductionmentioning
confidence: 99%
“…ICR can be induced by asymmetry in the nanopore geometry, as done in conically shaped nanopores, 2 as well as nanopores with a stepped cross section. 12 Asymmetric surface properties of nanopores, for example, asymmetric charge density, 13 wettability, 14 and slip length, 15 of surfaces along the pore axis can also produce ICR. Nanopores in contact with solutions that differed in conductivity achieved by concentration gradients 16 and viscosity gradients 17,18 were reported to exhibit current rectification as well.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their capability of simulating versatile charged conditions and responding to environmental changes, biologically inspired artificial nanopores are applied widely in many areas, including ionic current rectification (ICR), energy conservation, desalination, and sensing. Among these, ICR has been studied extensively in the past decades. This phenomenon refers to the diodelike behavior of a nanopore, where its ionic current–voltage relationship does not follow the conventional Ohm’s rule when the polarity is switched.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the diode-like ion current rectification (ICR) behavior, which assures ions preferentially transporting in one direction and hence amplifies ionic current, can be observed when the symmetry of ionic concentration profiles along the axis of a nanopore is broken [ 18 , 19 ]. Considerable experimental [ 20 , 21 , 22 ] and theoretical [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] efforts have been made on ICR in nanofluidics and all these studies concluded that the ICR property only can emerge in case the pore size is comparable to the EDL thickness.…”
Section: Introductionmentioning
confidence: 99%